- PENERAPAN ALGORITMA C.45 UNTUK KEPUTUSAN PEMBELIAN LAPTOP: - - Rika Harman (Computer Based Information System Journal, 2018)
The process of purchasing a laptop is not difficult enough to provide some money and go ketoko who sell it and buy a laptop. But there is a more difficult is to determine which laptop will be purchased in accordance with daily needs that is difficult, there are four major variables studied in the process of purchasing laptops in this journal is the processor, memory (RAM), hard drive and price. Researchers want to know by processing the data using software WEKA (Algortima C, 45) Which will be the main choice of buyers in buying a laptop which means it will be known which will be a top priority buyers in buying a laptop with the object is a student of SMK Batam city who has bought a laptop . From here it can be concluded later whether the buyer prefer the processor than the RAM, hard drive or price or other patterns will appear like RAM, processor, hard drive and the price or other patterns that can not be reviewed because all assumptions may appear depending on the data obtained. So please note that the conclusions are taken is not the most correct answer but based on the development of data obtained from students SMK processed using Software WEKA.